AI IN EDUCATION: RETHINKING THE TEACHER-STUDENT DYNAMIC IN DIGITAL CLASSROOMS - Zulkarnain Dama; Syafiq Amir; Arten Mobonggi (Al-Hijr: Journal of Adulearn World, 2026)
The integration of Artificial Intelligence (AI) in education is rapidly transforming traditional classroom dynamics, particularly the teacher-student relationship. AI tools, such as personalized learning platforms and automated grading systems, are increasingly utilized to enhance student engagement and optimize educational outcomes. However, these technologies also introduce challenges related to the evolving role of educators, particularly in maintaining human-centered teaching practices. This study explores how AI affects the teacher-student dynamic in digital classrooms, with a focus on the opportunities and challenges it presents to educators. The research employs a mixed-methods approach, combining surveys, interviews, and classroom observations across 10 institutions that have adopted AI-driven teaching tools. The results show that AI significantly enhances personalized learning and administrative efficiency, yet teachers express concerns about the depersonalization of interactions and the loss of emotional connections with students. The study concludes that while AI has the potential to improve teaching and learning, it is essential for educators to maintain their human role in fostering critical thinking, creativity, and emotional support. The research underscores the need for a balanced integration of AI into pedagogical strategies to ensure both technological efficiency and meaningful student-teacher interactions.